Controlled hypotension under rapid ventricular pacing technique in patients with cerebral arteriovenous malformation -a case report- - Zijian Zhao; Hang Wang; Xinxu Min; Zheng Li; Feng Feng (Korean Journal of Anesthesiology)
Background The transvenous approach to the treatment of cerebral arteriovenous malformation (AVM) is difficult and requires strict blood pressure and blood flow control; however, the cure rate is very high. Appropriate blood pressure control techniques can greatly benefit these patients. Case A 55-year-old male patient was found to have an aneurysm complicated with a cerebral AVM (length: 2.0 cm, width: 1.6 cm, height: 1.2 cm). Aneurysm embolization was considered for the first-stage surgery and transvenous AVM embolization for the second-stage surgery. Rapid ventricular pacing (RVP) provided a stable blood flow environment for the surgery, which was completed successfully. Conclusions RVP can thus provide an ideal condition for the embolization of cerebral AVM through the transvenous approach and can be a viable surgical option.